Gender Issues in Watershed Management - Wani, S.P.; Anantha, K.H.; Sreedevi, T.K. (SAGE Publications, 2014)
The rain-fed areas in the semi-arid tropics are characterised by low and erratic rainfall, severe land degradation, low crop yields and high poverty. Watershed programmes are recognised as a potential engine for agricultural growth and sustainable development in rain-fed areas (Wani et al., 2003). The success and sustainability of watershed programmes are directly related to collective action and community participation (Wani et al., 2008; Sreedevi and Wani, 2007). Women are key players as managers and direct actors in managing natural resources in the watershed and addressing household food security and nutritional goals. How ever, too often, they play a passive role in decision-making processes because of their low educational levels, social customs and economic dependence. Though women share a major workload for managing the natural resources, the benefits of the watershed programmes largely bypass them, except where targeted income-generating and employment interventions have been undertaken (Sreedevi et al., 2009)